Control of Complement Activation by the Long Pentraxin PTX3: Implications in Age-Related Macular Degeneration - Stravalaci, Matteo; Davi, Francesca; Parente, Raffaella; Gobbi, Marco; Bottazzi, Barbara; Mantovani, Alberto; Day, Anthony J.; Clark, Simon J.; Romano, Mario R.; Inforzato, Antonio (Frontiers in Pharmacology, 2020)
Dysregulation of the complement system is central to age-related macular degeneration (AMD), the leading cause of blindness in the developed world. Most of the genetic variation associated with AMD resides in complement genes, with the greatest risk associated with polymorphisms in the complement factor H (CFH) gene; factor H (FH) is the major inhibitor of the alternative pathway (AP) of complement that specifically targets C3b and the AP C3 convertase. Long pentraxin 3 (PTX3) is a soluble pattern recognition molecule that has been proposed to inhibit AP activation via recruitment of FH. Although present in the human retina, if and how PTX3 plays a role in AMD is still unclear. In this work we demonstrated the presence of PTX3 in the human vitreous and studied the PTX3-FH-C3b crosstalk and its effects on complement activation in a model of retinal pigment epithelium (RPE). RPE cells cultured in inflammatory AMD-like conditions overexpressed the PTX3 protein, and up-regulated AP activating genes. PTX3 bound RPE cells in a physiological setting, however this interaction was reduced in inflammatory conditions, whereby PTX3 had no complement-inhibiting activity on inflamed RPE. However, on non-cellular surfaces, PTX3 formed a stable ternary complex with FH and C3b that acted as a "hot spot" for complement inhibition. Our findings suggest a protective role for PTX3 in response to complement overactivation in AMD and point to a novel mechanism of complement regulation by this pentraxin with potential implications in pathology and pharmacology of AMD.